Microlayer formation and depletion beneath growing steam bubbles. (February 2019) - Hänsch, Susann; Walker, Simon
Highlights: The mechanistic formation and physically self-consistent depletion of microlayers beneath growing bubbles with heat conduction into the solid is demonstrated. Validation of the microlayer formation and ∼depletion model with recent measurements. Predictions are used to identify the circumstances and phenomena that cause microlayers to be generated. Predictions demonstrate that the importance of microlayers to bubble growth increases with the superheat. Investigation of the significance of evaporative thermal resistance for microlayer formation and evaporation. Abstract: Microlayers, the few-microns-thick layers of liquid that sometimes remain beneath bubbles growing on a heated substrate, are widely observed in experiments, but theoretical understanding of their formation, behaviour and role in bubble growth is limited. In this paper we present detailed interface-tracking simulations of the formation and depletion of such microlayers. Validation of our results is presented to the degree that available measurements of such a rapid and microscopic phenomenon allow. The work extends previous mechanistic hydrodynamic-only CFD simulations of early microlayer formation up to typical bubble departure times. These calculations confirm the understanding that the bubble growth rate and the resulting bubble shape determine the presence and overall extent of microlayers underneath steam bubbles. Their thickness is strongly influenced by viscous effects and surface tension. We then present coupled, physically self-consistent CFD simulations of the formation and evaporative depletion of such microlayers. This modelling suggests strongly that the evaporation process itself constitutes a significant fraction of the small resistance to heat and mass transfer presented by the very thin liquid layer. Inclusion of representations of evaporative thermal resistance, consistent with those suggested in the literature, is seen to promote the prediction of microlayer formation. Identification of the classes of conditions under which microlayers seem likely to be formed is presented, along with an assessment of their relative contributions to bubble growth. Comparisons of the predictions with recent detailed microlayer measurements indicate good agreement.